PENGARUH PENGAWASAN PIMPINAN, DISIPLIN DAN KOMPETENSI PEGAWAI PADA KINERJA PEGAWAI INSPEKTORAT KABUPATEN TABANAN - Herawati, Ni Luh Made; Dharma Suputra, I D.G.; Budiasih, I G.A.N. (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.07. TAHUN 2016, 2016)
The role of local Inspectorate as the Government Internal Supervisory Apparatus in monitoring and guidance in the financial statements cannot be separated from the performance of employees. Employee performance becomes an interesting phenomenon to study because many factors influencing it. The objective  of this study was to determine the influence of the leadership supervision, discipline and competence of the employees on the performance of Inspectorate employees in Tabanan Regency in terms of agency theory.  Purposive sampling method used in the determination of the sample, with the acquisition of a sample of 35 people. The collection of primary data through questionnaires distributed to 35 respondents. The research analyzed using multiple linear regregi showed that leadership supervision, discipline and competence of the employees have a positive influence on employee performance improvement Inspectorate Tabanan.
Keywords: supervision management, employee discipline, employee competence, employee performance